Changes in Statin Adherence Following an Acute Myocardial Infarction Among Older Adults: Patient Predictors and the Association With Follow‐Up With Primary Care Providers and/or Cardiologists. Issue 10 (19th October 2017) - Hickson, Ryan P.; Robinson, Jennifer G.; Annis, Izabela E.; Killeya‐Jones, Ley A.; Korhonen, Maarit Jaana; Cole, Ashley L.; Fang, Gang
Abstract : Background: Hospitalizations for acute myocardial infarctions (AMIs) are associated with changes in statin adherence. It is unclear to what extent adherence changes, which patients are likely to change, and how post‐discharge follow‐up is associated with statin adherence change. Methods and Results: This retrospective study used Medicare data for all fee‐for‐service beneficiaries 66 years and older with an AMI hospitalization in 2008–2010 and statin use before their index AMI. Multivariable multinomial logistic regression models (odds ratio [OR] and 99% confidence interval [CI]) were applied to assess associations between both patient characteristics and follow‐up with a primary care provider and/or cardiologist with the outcome of statin adherence change (increase or decrease) from the 6‐month pre‐ to 6‐month post‐AMI periods. Of 113 296 patients, 64.0% had no change in adherence, while 19.7% had increased and 16.3% had decreased adherence after AMI hospitalization. Black and Hispanic patients were more likely to have either increased or decreased adherence than white patients. Patients who required coronary artery bypass graft surgery (OR, 1.34; 99% CI, 1.21–1.49) or percutaneous transluminal coronary angioplasty/stent procedure (OR, 1.25; 99% CI, 1.17–1.32) during their index hospitalization were more likely to have increased adherence. Follow‐up with a primary care provider was only mildly associated with increased adherence (OR, 1.08; 99% CI, 1.00–1.16), while follow‐up with a cardiologist (OR, 1.15; 99% CI, 1.05–1.25) or both provider types (OR, 1.21; 99% CI, 1.12–1.30) had stronger associations with increased adherence. Conclusions: Post‐AMI changes in statin adherence varied by patient characteristics, and improved adherence was associated with post‐discharge follow‐up care, particularly with a cardiologist or both a primary care provider and a cardiologist.